ANALISA KEBUTUHAN LAHAN PARKIR PASAR PURI PATI - Rohman, Syamsul; Suwandi, Putri Anggi Permata; Yudaningrum, Farida (Jurnal Teknik Sipil Giratory UPGRIS, 2023)
Puri Market, which is located on Jalan Colonel Sunandar, precisely in the center of Pati Regency, is a traditional market which is the basis for the people of Pati to sell and buy all life-sustaining needs. This needs to be taken into account considering that the existence of an activity center must have as few parking areas as possible. Therefore, this study was carried out with the aim of providing recommendations for parking characteristics, parking space capacity and planning the most optimal parking layout for Puri Pati Market. Conditions are reviewed on 1 weekend and 3 weekdays. Namely Sunday, Monday, Wednesday and Thursday. From 06.00 to 12.00. The data used in this research are primary data and secondary data. The results of the research are that the characteristics of motorbike parking spaces for the Puri Pati Market area are 345 SRP which is in accordance with the 1996 Directorate General of Land Transportation standards. At Puri Pati Market There are also no entrances and exits that use electronic parking. With the existing motorbike parking space capacity of 280 SRP at Puri Pati Market, it can still meet existing parking needs. From the calculations that have been carried out, it is known that the need for motorbike parking space at Puri Pati Market is 345 SRP. In planning the parking layout using a 90Âº angle in the motorbike and car parking area as planned, namely being able to accommodate 280 motorbikes and 100 cars. With a comparison using an angle of 60Âº, we get only 152 motorbikes and 80 cars per plot.